Specification for a reconfigurable optoelectronic VLSI processor suitable for digital signal processing - Fey, Dietmar; et al. (Applied Optics, 1998)
A concept for a parallel digital signal processor based on optical interconnections and optoelectronic VLSI circuits is presented. It is shown that the proper combination of optical communication, architecture, and algorithms allows a throughput that outperforms purely electronic solutions. The usefulness of low-level algorithms from the add-and-shift class is emphasized. These algorithms lead to fine-grain, massively parallel on-chip processor architectures with high demands for optical off-chip interconnections. A comparative performance analysis shows the superiority of a bit-serial architecture. This architecture is mapped onto an optoelectronic three-dimensional circuit, and the necessary optical interconnection scheme is specified. © 1998 Optical Society of America.
UnivIS-Import:2015-03-05:Pub.1998.tech.IMMD.IMMD3.specif_4